Innovation impact in the textile industry: From the Toyota Production System to artificial intelligence - Carvalho, P. T. de.; Lopes, J. D.; Raimundo, R. J. (Sustainability, 2025)
The Toyota Production System (TPS) was a revolutionary approach to automobile production that influenced companies all over the world. The fight against redundancy is at the core of this approach. The textile industry remains one of the most polluting sectors worldwide, which makes environmental sustainability a key concern. In line with national priorities, companies are striving to balance profitability with sustainability, minimizing defects and reducing waste. This study explores the evolution of textile production systems from TPS principles to the integration of Artificial Intelligence (AI) and how they can be used from a sustainability perspective. Smartex, a textile start-up recognized as the winner of the Web Summit 2021 competition, was chosen as the focus of this case study. Employing qualitative research methods, including content analysis of interviews, management reports and website data, the study examines the parallels and distinctions between TPS and Smartex’s AI-driven system. The findings highlight how Smartex is revolutionizing the textile industry by leveraging AI to avoid defects and reduce waste, advancing both environmental and commercial objectives. Finally, the implications and limitations of the research are explained.